Serum sphingolipids level as a novel potential marker for early detection of human myocardial ischaemic injury - Egom, Emmanuel E.; mamas, mamas; Chacko, Sanoj; Stringer, Sally E.; El-Omar, Magdi; Chirico, Debora; Clarke, Bernard; Neyses, Ludwig; Cruickshank, Kennedy; Lei, Ming; Fath-Ordoubadi, Farzin (Frontiers in Physiology, 2013)
Background: Ventricular tachyarrhythmias are the most common and often the first manifestation of coronary heart disease and lead to sudden cardiac death. Early detection/identification of acute myocardial ischaemic injury at risk for malignant ventricular arrhythmias in patients remains an unmet medical need. In the present study, we examined the sphingolipids level after transient cardiac ischaemia following temporary coronary artery occlusion during percutaneous coronary intervention (PCI) in patients and determined the role of sphingolipids level as a novel indicator for early detection of human myocardial ischaemic injury. Methods and Results:Venous samples were collected from either the coronary sinus (n=7) or femoral vein (n=24) from 31 patients aged 40-73 years-old at 1, 5 min and 12h, following elective PCI. Plasma sphingolipids levels were assessed by HPLC. At 1 min coronary sinus levels of sphingosine 1-phosphate (S1P), sphingosine (SPH) and sphinganine (SA) were increased by 314%, 115% and 614%, respectively (n=7), while peripheral blood levels increased by 79%, 68% and 272% (n=24). By 5 min, coronary sinus S1P and SPH levels increased further (720%, 117%), as did peripheral levels of S1P alone (792%). Where troponin T was detectable at 12 h (10 of 31), a strong correlation was found with peak S1P (R2=0.818; P<0.0001). Conclusion: For the first time, we demonstrate the behaviour of plasma sphingolipids following transient cardiac ischaemia in humans. The observation supports the important role of sphingolipids level as a potential novel marker of transient or prolonged myocardial ischaemia.